HOLISTIC APPROACH OF AYURVEDA IN THE MANAGEMENT OF EKA-KUSHTHA W. S. R. TO PSORIASIS - A CASE STUDY (AYUSHDHARA, 2021)
Skin is the largest organ which reflects the both healthy and diseased condition of the body. According to ancient Ayurved samhitas, all the skin diseases are categorized under Kushtha roga. In modern world, skin has greater cosmetic importance leading to boost the confidence and personality of an individual as well as to attain the healthy mindset. The morbid condition of the skin should be treated earlier as it may attain Krichrasadhya or even Asadhya avastha also. Ancient Acharyas have been explained in detail the Panchakarma accompanying with variety of Shamana aushadhis and Sthanika chikitsa to treat the Kushtha rogas. In the present case study, a 37 years old female patient having symptoms resembling to Eka kushtha was treated with combine use of ancient Ayurvedic treatment protocols viz., Nidana parivarjana, Shodhana chikitsa, Shamana aushadhis and Sthanika chikitsa together with Pathyapathya. The assessment of Lakshanas was done by using WHO guidelines for Kushtha. This comprehensive approach of Ayurveda to treat the Eka kushtha helps to achieve the significant relief in symptoms of the patient.